Theory and practice of real estate valuation in developing countries: a case study of Kenya - Cheloti, Irene Naliaka (Department of Construction Economics and Management, 2023)
Valuation problems in practice, including valuation inaccuracies/variations, client influence and inappropriate use of heuristics, negatively impact the valuation profession globally. These problems persist despite efforts by professional bodies and researchers worldwide to improve the practice of valuation. The above valuation problems are more pronounced in developing countries compared to their counterparts in developed nations. The persistence of valuation problems in developing countries has mainly been attributed to the current strategies that address these problems in the context of valuer conduct, neglecting market-related issues and problems related to the normative basis of the standard valuation theory. These strategies are borrowed from developed countries, which are characterised by a lot of information, yet the imperfect nature of the property market in developing countries differs from that of developed nations. Like in other developing countries, valuation problems exist in Kenya and persist despite efforts to minimise them. The main objective of this study is to examine theory and practice of real estate valuation in Kenya, with a view to establish why valuation problems persist despite efforts to minimise them. The study utilised mixed methods research design incorporating both qualitative and quantitative research methods. This involved a survey and experiment of registered and practicing valuers in Kenya and interviews of key informants within universities that offer real estate degree courses, commercial banks, the ISK, the RICS, and the VRB. The main finding of this study is that valuation problems in developing countries mostly result from the imperfect nature of the property market in these nations, i.e., market-related problems followed by valuers' conduct which is the focal point of most empirical studies in valuation. The said valuation problems can be categorised as market-related problems, valuer conduct, and problems related to the normative basis of the standard valuation theory. While efforts to address valuation problems in the context of valuer conduct are essential, it is recommended that significant efforts, including valuation research, be directed towards addressing market-related issues; a core problem of the valuation profession in Kenya and probably other developing countries. In similar vein, it is recommended that further research be directed at exploring the application and implication of alternative theoretical frameworks. The study has made diverse contributions to the existing body of knowledge in theoretical, empirical, methodological, and policy development terms. More importantly, the study expands empirical literature on theory and practice of real estate valuation in developing countries.